“Stress Redistribution And Deformation Behavior In Twin Tunnels: A Comparative Analysis Of Intact And Jointed Rock Mass Under Sequential Excavation Condition" (International Journal of Environmental Sciences, 2025)
This study investigates the stress redistribution and deformation behavior in twin horse-shoe shaped tunnels under sequential excavation conditions, comparing intact and jointed rock masses. Using finite element software RS2, the research evaluates the influence of pillar width-to-diameter ratios (W/D = 0.3, 0.6, 1.2) and in-situ stress conditions (K₀ = 0.5, 1.0, 1.5) on tunnel stability and surrounding rock mass behavior. The analysis incorporated elasto-plastic behavior using the Hoek-Brown failure criterion for rock mass and Barton’s model for jointed rock strength characterization. Results reveal that lower W/D ratios (0.3) and higher K₀ values (1.5) significantly amplify deformation differences, particularly at critical locations such as the springing level on the pillar side and the center of the pillar zone, where differences exceed 900%. Conversely, higher W/D ratios (1.2) minimized interaction effects and deformation discrepancies. The jointed rock mass exhibits more pronounced deformations compared to intact rock, emphasizing the role of discontinuities in tunnel stability. The findings provide critical insights for optimizing tunnel design and construction practices in challenging geological conditions, ensuring structural integrity and minimizing ground settlements.